Advances in MRI around metal. Issue 4 (25th March 2017) - Jungmann, Pia M.; Agten, Christoph A.; Pfirrmann, Christian W.; Sutter, Reto
Abstract : The prevalence of orthopedic metal implants is continuously rising in the aging society. Particularly the number of joint replacements is increasing. Although satisfying long‐term results are encountered, patients may suffer from complaints or complications during follow‐up, and often undergo magnetic resonance imaging (MRI). Yet metal implants cause severe artifacts on MRI, resulting in signal‐loss, signal‐pileup, geometric distortion, and failure of fat suppression. In order to allow for adequate treatment decisions, metal artifact reduction sequences (MARS) are essential for proper radiological evaluation of postoperative findings in these patients. During recent years, developments of musculoskeletal imaging have addressed this particular technical challenge of postoperative MRI around metal. Besides implant material composition, configuration and location, selection of appropriate MRI hardware, sequences, and parameters influence artifact genesis and reduction. Application of dedicated metal artifact reduction techniques including high bandwidth optimization, view angle tilting (VAT), and the multispectral imaging techniques multiacquisition variable‐resonance image combination (MAVRIC) and slice‐encoding for metal artifact correction (SEMAC) may significantly reduce metal‐induced artifacts, although at the expense of signal‐to‐noise ratio and/or acquisition time. Adding advanced image acquisition techniques such as parallel imaging, partial Fourier transformation, and advanced reconstruction techniques such as compressed sensing further improves MARS imaging in a clinically feasible scan time. This review focuses on current clinically applicable MARS techniques. Understanding of the main principles and techniques including their limitations allows a considerate application of these techniques in clinical practice. Essential orthopedic metal implants and postoperative MR findings around metal are presented and highlighted with clinical examples. Level of Evidence: 4 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2017;46:972–991.